Medicinal plants of district Bijnor (U.P.) India with special reference to their folk medicinal uses - Chaudhary*, Shalu (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Present communication deals with the study of medicinal plant of Bisnor district (U.P.), India special reference to their folk medicinal uses.